PENGHITUNGAN BIOMASSA DAN KARBON DI ATAS PERMUKAAN TANAH DI HUTAN LARANGAN ADAT RUMBIO KAB KAMPAR - Nasib Tuah; Rudianda Sulaeman; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Forests are natural resources that can absorb carbon dioxide (CO2) in the process of photosynthesis, and convert it into carbohydrates and store them into biomass. Prohibition of indigenous Rumbio forest areas is one area of forests managed by communities’ customary law, which is the existence of indigenous forest to gain recognition by the State which has the right to control all resources. In order, it needs to know how big the potential of carbon. The study aims to determine the potential of biomass and carbon on the ground in Indigenous of Rumbio Forest. Mechanical determination of the plot and data is done by Stratified Random Sampling, which is the method of taking the sample based on strata (levels). The potential of biomass on the ground biomass is done by summing the litter, nursery, lowers plants, saplings, poles and trees that use formula algometric. Biomass litter and plant seedlings under estimated by using the Indonesian National Standard. Carbon stored value is 0.47 of biomass. The results showed that the carbon potential in the area ofIndigenous of Forests Rumbio forest is 31922.21 ton / ha. Keywords: forest, forest customary prohibition, biomassa, carbon